Changes in Ocular Surface and Precorneal Tear Film in Tobacco Smokers: Doi: 10.36351/pjo.v39i4.1558 - Jahan Zaib, Hafiz Muhammad; Khalid, Amina; Khan, Ijaz; Nazir, Fahmina; Khan, Nida Armoghan (Pakistan Journal of Ophthalmology, 2023)
Purpose: To determine the changes in “ocular surface” and “pre-corneal tear film” in tobacco smokers. Study Design: Cross sectional, comparative. Place and Duration of Study: Holy Family Hospital, Rawalpindi Medical University, Rawalpindi, Pakistan from February 2022 to May 2022. Methods: Eighty four patients (42 smokers and 42 non-smokers) were selected for ocularevaluation. “Ocular surface” and “pre-corneal tear film” were assessed by “tear film break up time (TBUT)”, “Schirmer test”, “corneal punctate staining” and “corneal/conjunctival sensitivity” in both smokers and non-smokers. Chi square test and unpaired t-test were applied and p ≤ 0.05 was taken as significant. Results: Meanage of participants was 36.07 ± 5.75 years. There were 76.2% males and 23.8% females. In terms of age and gender, there was no statistically significant difference between smokers and non-smokers. In terms of TBUT (p = 0.000), corneal punctate staining (p = 0.000) and corneal/conjunctival sensitivity (p = 0.000) values were significantly lower in smokers as compared to non-smokers while in terms of “Schirmer test” there was no statistically significant difference between smokers and non-smokers (p-value of 0.827). Conclusion: Use of cigarettes results in multiple adverse effects in the “ocular surface” and “pre-corneal tear film” including unstable tear film, dry eyes, poor sensitivity of cornea as well as the conjunctiva making their eyes more prone to damage and disease.